1995
DOI: 10.1111/j.1540-4781.1995.tb05417.x
|View full text |Cite
|
Sign up to set email alerts
|

Cognition Plus: Correlates Of Language Learning Success

Abstract: This article examines the relationships of a variety of individual difference variables to end‐of‐training proficiency ratings in speaking and reading for a large sample of adults in intensive training in a wide range of languages at the U.S. Department of State. Variables included tested cognitive aptitude, learning strategies, learning styles, personality, motivation, and anxiety. Although tested cognitive aptitude showed the strongest correlations with proficiency test results in both skills, the other vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
191
3
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 376 publications
(216 citation statements)
references
References 33 publications
(27 reference statements)
19
191
3
3
Order By: Relevance
“…In Onwuegbuzie, Bailey, and Daley's (2000) study, students' perceptions of their own ability, intelligence, and academic competence (high or low self-confidence vs. language anxiety) were associated with language performance. Their results are the same as Ehrman and Oxford's (1995) findings that students' self-perceptions of their academic and foreign language competence (high or low self-confidence) significantly affected their foreign language achievement.…”
Section: Self-confidencesupporting
confidence: 78%
See 1 more Smart Citation
“…In Onwuegbuzie, Bailey, and Daley's (2000) study, students' perceptions of their own ability, intelligence, and academic competence (high or low self-confidence vs. language anxiety) were associated with language performance. Their results are the same as Ehrman and Oxford's (1995) findings that students' self-perceptions of their academic and foreign language competence (high or low self-confidence) significantly affected their foreign language achievement.…”
Section: Self-confidencesupporting
confidence: 78%
“…Other studies also support the belief that self-confidence is an important factor for successful language learning (e.g., Casado & Dereshiwsky, 2004;Ehrman & Oxford, 1995;Matsuda & Gobel, 2004;Onwuegbuzie, Bailey, & Daley, 1999, 2000Ro, 2013). For instance, Matsuda and Gobel's (2004) research on language anxiety and performance in the foreign language classroom reported that self-confidence is an important factor in language performance in the classroom of first-year college students in Japan.…”
Section: Self-confidencementioning
confidence: 66%
“…Despite the fact that a large number of studies have shown that anxious language learners are less successful at language learning, in several other studies anxiety has been found to help improve performance in language learning (Ehrman & Oxford, 1995;Young, 1992). Neutral relationships have also been found.…”
Section: Theory and Practice In Language Studiesmentioning
confidence: 78%
“…Thus, many choose to remain silent in class and thus their oral proficiency in the target language just falls down or becomes lower, as found in Liu's [12,13] studies. Meanwhile, all types of SL/FL anxiety have been evidenced to be correlated to confidence and self-esteem, 2 Education Research International attitude, motivation, and cultural differences, and so forth [3,6,12,14,22].…”
Section: Introductionmentioning
confidence: 99%